2022
DOI: 10.33830/jom.v18i2.3278.2022
|View full text |Cite
|
Sign up to set email alerts
|

Female Board Independency in Corporate Governance and Firm Performance Students

Abstract: Purpose  – This research examines female board independence and influence on company performance. The concept of female leaders in work should be discussed since gender inequality assumes that they are considered not socially accepted, have a non-business background, and are appointed due to nepotism. Methodology – The research uses a quantitative approach - research data from companies listed on the Indonesia Stock Exchange in the KOMPAS100 index from August 2021 to January 2022. The data was collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The single-country research for Southeast developing economies shows female diversity increased firm performance for Malaysian firms in 2010-2014 (Rahman et al, 2022) and Indonesian firms in 2011-2016 (Pasaribu et al, 2019). Conversely, female diversity decreased firm performance for Sri Lanka firms in 2006-2010 (Wellalage & Locke, 2013), Indonesia firms in 2011-217 2015 (Tarigan et al, 2018), and Indonesia firms in 2014-2020 (Septiana et al, 2022). Based on previous research, research with research objects in Indonesia which had previous studies, showed conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The single-country research for Southeast developing economies shows female diversity increased firm performance for Malaysian firms in 2010-2014 (Rahman et al, 2022) and Indonesian firms in 2011-2016 (Pasaribu et al, 2019). Conversely, female diversity decreased firm performance for Sri Lanka firms in 2006-2010 (Wellalage & Locke, 2013), Indonesia firms in 2011-217 2015 (Tarigan et al, 2018), and Indonesia firms in 2014-2020 (Septiana et al, 2022). Based on previous research, research with research objects in Indonesia which had previous studies, showed conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The progress of a company will be intricately linked to its corporate governance (Kyere & Ausloos, 2021). Corporate governance actively safeguards the well-being of stakeholders, acknowledging its potential impact on the company (Septiana et al, 2022). This encourages companies to modify their corporate governance practices to enhance shareholder goals, as there is evidence suggesting that in firms with robust corporate governance, investors are willing to pay a substantial premium for company shares.…”
Section: Introductionmentioning
confidence: 99%